Effect Observation on Quanjing Acupuncture combined with Blood-letting Cupping Therapy on Upper Extremity Spasticity in Recovery Stage of Stroke - Zhulian ZHAN; Lu YANG; Mali XI; Xiaoying HU; Guoping ZHOU (康复学报)
Objective:To observe the effect of Quanjing acupuncture combined with blood-letting cupping therapy on upper limb spasticity in recovery stage of stroke.Methods:A total of 110 patients with stroke at recovery stage were randomly divided into control group and treatment group, with 55 cases in each group. The control group received routine diagnosis and rehabilitation treatment, and Quanjing acupuncture treatment, once a day, six times a week, two weeks in each course, continuous treatment for two courses; the treatment group was treated combined with blood-letting cupping therapy on the basis of the control group, once every other day, three times a week, two weeks in each course, continuous treatment for two courses.Modified MAS scale was used to evaluate the degree of upper limb spasm;simplified Fugl-Meyer motor function scale (FMA) was used to assess the limb motor function of patients; Barthel index (BI) was used to assess the daily living ability of patients.Results:Compared with the treatment before, MAS score of both groups was significantly lower, FMA score and BI score were significantly higher, with statistically significant difference (P<0.05); Compared with the control group, MAS score of the treatment group decreased more significantly after treatment, FMA score and BI score improved more significantly, with statistically significant difference (P<0.05);the effective rate of spasm improvement in the treatment group was significantly higher than that in the control group, with statistically significant difference (P<0.05).Conclusion:Quanjing Acupuncture therapy combined with blood-letting cupping therapy can improve the degree of upper limb spasm, motor function and daily living ability of stroke patients at recovery stage, and has a good clinical effect.